2009
DOI: 10.2527/jas.2008-1420
|View full text |Cite
|
Sign up to set email alerts
|

Corn oil or corn grain supplementation to steers grazing endophyte-free tall fescue. II. Effects on subcutaneous fatty acid content and lipogenic gene expression1

Abstract: Twenty-eight Angus steers (289 kg) were finished on a high-concentrate diet (85% concentrate: 15% roughage; CONC), or endophyte-free tall fescue pastures with corn grain supplement (0.52% of BW; PC), corn oil plus soybean hull supplement (0.10% of BW corn oil plus 0.45% of BW soybean hulls; PO), or no supplement (pasture only; PA). Subcutaneous adipose tissues were processed for total cellular RNA extraction and fatty acid composition by GLC. Relative expression of genes involved in lipogenesis [fatty acid syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
62
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 48 publications
8
62
2
Order By: Relevance
“…Heifers assigned to MI had greater (P = 0.01) mRNA expression of FASN on day 51 compared with CON heifers (Table 6); an enzyme that modulates de novo lipogenesis and is up-regulated by rate of nutrient intake (Duckett et al, 2009). Moreover, MI heifers had greater mean mRNA expression of subcutaneous adipocyte PPARγ (P = 0.05), which regulates adipocyte development via triglyceride uptake (Rosen and MacDougald, 2006), and hepatic IGF-I (P < 0.01) compared with CON heifers (Table 6).…”
mentioning
confidence: 99%
“…Heifers assigned to MI had greater (P = 0.01) mRNA expression of FASN on day 51 compared with CON heifers (Table 6); an enzyme that modulates de novo lipogenesis and is up-regulated by rate of nutrient intake (Duckett et al, 2009). Moreover, MI heifers had greater mean mRNA expression of subcutaneous adipocyte PPARγ (P = 0.05), which regulates adipocyte development via triglyceride uptake (Rosen and MacDougald, 2006), and hepatic IGF-I (P < 0.01) compared with CON heifers (Table 6).…”
mentioning
confidence: 99%
“…The decreased n-3/n-6 ratio in grazing beef is a consequence of increased ALA proportion and a relative constant proportion of LA in adipose tissues from steers on pasture compared with those finished with feedlot diets. Steers finished on a grain diet show a 2.5 times higher n-6/n-3 PUFAs ratio than those finished on pasture (Basarab et al, 2007;Duckett et al, 2009). However, the fold of increase in the n-6/n-3 FA ratio can be higher when examined in beef muscles (Garcia et al, 2008).…”
Section: Discussionmentioning
confidence: 91%
“…4 The changes in these fatty acid composition of the subcutaneous adipose tissue suggest that de novo lipogenesis, desaturase, and elongase activities in the adipocytes were heightened with corn grain supplementation. Duckett et al 11 reported 46-fold and 18-fold upregulation of SCD-1 mRNA expression in subcutaneous adipose tissue in steers finishing on high-concentrate diets (85% corn grain) or corn grain supplementation (0.5% of body weight/d), respectively, compared with steers finished on pasture only. Exposure to corn grain during the finishing phase of beef production increases adipocyte hypertrophy and lipogenic enzyme activities to alter fatty acid composition.…”
Section: Discussionmentioning
confidence: 99%
“…10 Corn grain supplementation to grazing steers can also alter fat deposition, fatty acid composition and lipogenic gene expression of adipose tissue depots. 11,12 Fat deposition in finishing animals is the result of both hyperplasia and hypertrophy. [13][14][15] We hypothesized that the nutritional milieu of the donor animals from which SV cells were isolated from would alter proliferative, adipogenic, and lipogenic capacity of preadipocytes/adipocytes.…”
Section: Introductionmentioning
confidence: 99%